Use of GIS and remote sensing in identifying recharge zones in an arid - Sen, Pawanh Kumar; Gieske, Ambro (Journal of Nepal Geological Society, 2006)
A water balance model for the Roxo catchment in Portugal was developed based on ground data and satellite imageries. The model used the Thornthwaite-Mather method of analysing the recent (2001–2003) climatological records. The amount of annual runoff from the catchment predicted by the model is 29 million m3, which is accumulated in the Roxo reservoir. Almost all the discharge is contributed by the direct runoff and the groundwater contribution is insignificant. However, there are some groundwater recharge zones in the northern part of the catchment. With the help of remote sensing and geographic information system, it was possible to identify the groundwater recharge zones in an arid region like the Roxo catchment, where the traditional one-point calculation method failed to give any results.